Sulfonated polyaniline coated bamboo-derived biochar/sulfur cathode for Li-S batteries with excellent dual conductivity and polysulfides affinity. (1st July 2019) - Wei, Yiqi; Yan, Yinglin; Zou, Yiming; Shi, Mangmang; Deng, Qijiu; Zhao, Nana; Wang, Juan; You, Caiyin; Yang, Rong; Xu, Yunhua
Abstract: The sulfonic acid group exhibits considerable ion affinity. The present work therefore synthesizes, a core-shell composite material having a sulfonated polyaniline shell, and a bamboo-derived porous carbon core loaded with sulfur. The thin, homogeneous shell has a thickness of approximately 20 nm. This composite is employed as a cathode material in Li-S batteries and the electrochemical properties of these devices are systematically investigated. This cathode (containing 64.0 wt% S) exhibits a higher initial discharge capacity (1484 mAh g −1 at 0.1 C), improved cycling stability (853 mAh g −1 after 100 cycles at 0.1 C), and remarkable rate performance (810.2, 682.7 and 353.0 mAh g −1 at 2, 3 and 5 C, respectively). These values are superior to those obtained using a polyaniline shell. Electrochemical impedance spectroscopy and density functional theory calculations are used to elucidate the internal mechanisms of the sulfonated polyaniline shell during cycling. The calculated results demonstrate that the shell possesses extremely high electron and Li ion conductivities, and so enhances the redox reaction kinetics during long-term cycling. It also physically confines and chemically anchors polysulfides, thus limiting the shuttle effect. This cathode design is expected to assist in the future commercialization of Li-S batteries. Graphical abstract: Image 1